A methodology to evaluate the effectiveness of designers' cognitive process when using multi-user virtual reality / Adlin Shaflina Azizo ... [et al.] - Azizo, Adlin Shaflina; Ali, Kherun Nita; A. Iahad, Noorminshah; Mohd, Norhazren Izatie; Mat Dzahir, Mohd Azwarie; Abdul Rahiman, Nafisah (UiTM Press, 2022)
This paper proposed the mixed-mode methodology to evaluate the effectiveness of the cognitive process when using Multi-user Virtual Reality (VR) in the design review sessions. The research explains that the design review is essential for the planning process since it evaluates the client's requirements against the designers' design before the construction starts. Quality communication among the designers and clients plays a central role in enhancing the output of the design review session, apart from the quality of visualisation during the presentation. A multi-user VR system with a head-mounted display allows users to fully immerse in the virtual environment (VE) during the design review process and achieve quality discussion and decision-making. This paper describes the process of data collection in quantitative and qualitative methods, where questionnaires will be distributed to determine the state-of-the-art of the designers' cognitive processes when they are involved in the design review session. Parallelly, an experiment on the use of multi-user VR during a design review session will be conducted. Users (Designers) will be interviewed before and after the experiment. Finally, multi-user VR's effectiveness will be identified by comparing the findings from both quantitative and qualitative methods.